Monopole-Antimonopole Pair, Vortex Dyons Of The SU(2) Yang-Mills-Higgs Field Theory - Lim , Kok Geng (2011)

(untitled)
Magnetic monopoles and dyons are topological soliton solutions in three space dimensions, which arise in Yang-Mills-Higgs gauge theory where the non-Abelian gauge group SU(2) is spontaneously broken by the Higgs eld to a residual symmetry group U(1). While the magnetic charge is quantized due to topological arguments, the electric charge is not. In this thesis, the magnetic monopoles and dyons are studied in the context of the SU(2) Yang-Mills-Higgs eld theory which is also known as the SU(2) Georgi- Glashow model.